2010
DOI: 10.1111/j.1440-1843.2009.01679.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pulmonary diseases in common variable immunodeficiency and X‐linked agammaglobulinaemia

Abstract: Patients with CVID had a greater likelihood of developing lung disease, possibly due to delayed diagnosis and immune dysregulation, as compared with XLA patients. Early diagnosis of patients with primary antibody deficiencies and adequate i.v. immunoglobulin replacement therapy substantially reduces the number of pulmonary infections. However, CVID patients are prone to progression of lung disease despite optimal immunoglobulin therapy because of the nature of the disease. This important issue should be addres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 63 publications
(139 reference statements)
4
39
0
1
Order By: Relevance
“…The incidence of bronchiectasis in patients with XLA is almost 32%, although XLA has been associated with up to 3% of cases of childhood bronchiectasis [73][74][75] and is rare in adults. We indicated that the rate and severity of bronchiectasis were greater in CVID patients than in those with XLA, probably because of the earlier diagnosis and treatment of XLA patients [76]. Moreover, CVID patients had a greater likelihood of developing lung disease, possibly owing to delayed diagnosis and immune dysregulation, as compared with XLA patients [76].…”
Section: Bronchiectasismentioning
confidence: 77%
See 1 more Smart Citation
“…The incidence of bronchiectasis in patients with XLA is almost 32%, although XLA has been associated with up to 3% of cases of childhood bronchiectasis [73][74][75] and is rare in adults. We indicated that the rate and severity of bronchiectasis were greater in CVID patients than in those with XLA, probably because of the earlier diagnosis and treatment of XLA patients [76]. Moreover, CVID patients had a greater likelihood of developing lung disease, possibly owing to delayed diagnosis and immune dysregulation, as compared with XLA patients [76].…”
Section: Bronchiectasismentioning
confidence: 77%
“…We indicated that the rate and severity of bronchiectasis were greater in CVID patients than in those with XLA, probably because of the earlier diagnosis and treatment of XLA patients [76]. Moreover, CVID patients had a greater likelihood of developing lung disease, possibly owing to delayed diagnosis and immune dysregulation, as compared with XLA patients [76]. Mild to severe vitamin D deficiency in CVID patients is considered to be associated with a risk of bronchiectasis.…”
Section: Bronchiectasismentioning
confidence: 82%
“…Hypogammaglobulinemia or antibody deficiency is the major hallmark of PAD patients. Affected individuals share a clinical phenotype with common features, such as chronic and recurrent infections, chronic inflammation, and autoimmunity [2], leading to recurrent hospitalization and a decreased quality of life [3,4,5]. …”
Section: Introductionmentioning
confidence: 99%
“…98 Clinically, patients present with recurrent pyogenic sinopulmonary infections in the second or third decades of life; this later presentation could account for the higher incidence of lung disease seen with CVID when compared with XLA. 99 Bronchiectasis and lymphoid interstitial pneumonitis may develop and there is also an increased risk of autoimmune disease and malignancy. The development of bronchiectasis is aided by unregulated inflammation intrinsic to the disease as well as a low number of IgM memory B cells and reduced IgM anti-pneumococcal polysaccharide antibodies seen in a subset of these patients noted to be at higher risk for recurrent encapsulated bacterial infections.…”
Section: Disorders Of Humoral Immunitymentioning
confidence: 99%